Composition control of quinary GaInNAsSb alloy grown by molecular beam epitaxy. Issue 11 (18th October 2013) - Miyashita, Naoya; Ahsan, Nazmul; Islam, Muhammad Monirul; Okada, Yoshitaka; Yamaguchi, Hiroshi; Kumakura, Kazuhide
Abstract In order to precisely control the composition of quinary GaInNAsSb alloy, we investigated the incorporation behavior of constituent atoms during atomic hydrogen‐assisted molecular beam epitaxial growth. The nitrogen (N) composition, in comparison of GaNAs and GaNAsSb, increased by the supply of antimony (Sb). However, addition of indium (In) decreases the N composition during Sb mediated growth of GaInNAsSb, which enables obtaining the same N composition when an adequate In composition is chosen. It was revealed that Sb incorporation was increased when (i) In composition decreased, (ii) Sb flux increased, (iii) growth temperature decreased, and (iv) growth rate increased. These results are thought to be related to the effect of competitive role among strain, coverage, desorption, and segregation. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)